PENGARUH BIAYA PRODUKSI TERHADAP LABA BERSIH PT PANAMA MEGAH JAYA BANDUNG PERIODE 2015-2019: PENGARUH BIAYA PRODUKSI TERHADAP LABA BERSIH - Bisma Indrawan; Nurul Aqidhah (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2022)
Abstract This study aimed to determine the effect of production cost on the net profit of PT. Panama Megah Jaya Bandung in the period of 2015-2019. This study used quantitative methods with data collection techniques in the form of literature study, observation, and interviews. Data analysis using normality test. Based on the results of research, it can be concluded that the variable X (Production Cost) and Variable Y (Net Profit) have a high correlation relationship of 0.772 (Pearson product moment). The coefficient indicates that the production cost affects only 59.6% of net profit and the remaining 40.4% is influenced by other factors not examined by the author. For the measurement of the T-test, the t-value is 2.104 and the t-table is 3.182, then 2.104 < 3.182 Ho is accepted and Ha is rejected, meaning that there is no significant effect between production costs on the net profit. As for the problems faced in the study, is that in 2018 there was a decrease in net profit by 18% which was due to a decrease in sales and an increase in income tax expenses, if the dollar value increased and the currency value decreased, and the instability of the presence of production employees. Efforts to overcome these problems are that the company must increase its production volume and increase the number of sales. To increase sales, this can be done by improving marketing strategies, for example through advertising, creating product innovations, and so on. Make a selective order using a minimum price. Create a comfortable work environment, incentives for full attendance employees. Keywords : Production Costs; Net Profit